Prevalence of sarcopenia in multi ethnics adults and the association with cognitive impairment: findings from West-China health and aging trend study - Xiaolei Liu; Lisha Hou; Xin Xia; Yang Liu; Zhiliang Zuo; Yan Zhang; Wanyu Zhao; Qiukui Hao; Jirong Yue; Birong Dong (BMC Geriatrics, 2020)
Abstract Background Sarcopenia is a condition that is characterized by loss of muscle mass, muscle strength and muscle functional impairment with ageing. It is associated with poor health outcomes, premature death and a significant burden on the global health economy. The prevalence of sarcopenia in China is unknown since most of the studies are lack of uniform standard. The study was undertaken to study the prevalence of sarcopenia and the association with cognitive impairment among multi-ethnic adults aged 50 years old or older in western China. Methods We measured gait speed, handgrip strength and muscle mass by using bioelectrical impedance analysis (BIA) for all eligible participants and 4500 participants were eligible for the analysis. We defined sarcopenia using the diagnostic algorithm recommended by the Asian Working Group for Sarcopenia (AWGS). We assessed the participants’ cognitive functions using the 10-item Short Portable Mental Status Questionnaire (SPMSQ). Relationships between sarcopenia and cognitive impairment were analyzed using univariate and multivariate analyses. Results Of 4500 participants (mean age 62.4 ± 8.3 years), 869 (19.31%) adults were sarcopenia. 446 (9.9%) participants were identified as having mild cognitive impairment, 144 (3.2%) adults were identified as having moderate/severe cognitive impairment. After adjusting for age, gender, ethnics and other potential cofounders, cognitive impairment was found to be independently associated with sarcopenia with a dosage effect (mild cognitive impairment: odds ratio [OR]: 1.41, 95% CI 1.10–1.82; moderate/severe cognitive impairment: OR: 3.05, 95% CI 2.08–4.49). After gender stratification, the association between mild cognitive impairment with sarcopenia in male is not significant, while is still significant in female. While the association between moderate/severe cognitive impairment is independently associated with sarcopenia in both male and female. Conclusions The prevalence rates of sarcopenia, mild cognitive impairment, moderate/severe cognitive impairment among the communities aged 50 or older in western China were 19.31, 9.9 and 3.2%, respectively. Cognitive impairment was significantly associated with sarcopenia with a dosage effect, especially in female.